A Study on Banking Service Quality in Nagapattinam District, Tamil Nadu - Ananth, A.; Arulraj, A. (Indian Journal of Marketing, 2011)
Three forces dominate the prevailing marketing environment in the service sector: Increasing competition from private players, changing and improving technology and continuous shifts in the regulatory environment, which has led to the growing customer sophistication. Customers have become more and more aware of their requirements and demand higher standard of service. Their perception and expectations are continually evolving, making it difficult for the service providers to measure and manage service effectively. The key lies in improving the service selectively, paying attention to more critical service attributes/dimensions as a part of customer service management. The present study identifies ten dimensions for measuring service quality in Nagapattinam District. There are seven taluks and 120 branches in Nagapattinam district. The study will help the bankers to enhance their quality of service and make the customers loyal to the organization. The study used simple random sampling method to collect 170 data from the banking customers in Nagapattinam and data were analyzed through Amos 16 and found that the Credit scheme and Interest rate is the mediating factor to service quality.